2022
DOI: 10.1021/acs.est.1c07048
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene–Chlorine Oxidation in the Presence of NOx and Implications for Urban Atmospheric Chemistry

Abstract: Fine particulate matter (PM2.5) is a key indicator of urban air quality. Secondary organic aerosol (SOA) contributes substantially to the PM2.5 concentration. Discrepancies between modeling and field measurements of SOA indicate missing sources and formation mechanisms. Recent studies report elevated concentrations of reactive chlorine species in inland and urban regions, which increase the oxidative capacity of the atmosphere and serve as sources for SOA and particulate chlorides. Chlorine-initiated oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…In addition to molecular chlorine and nitryl chloride, we observed a variety of organic species in the gas and particle phases, including oxygenated organics (compounds with the molecular formula C x H y O z , abbreviated as CHO); chlorinated organics (C x H y Cl i O z , abbreviated as CHClO); and nitrogen-containing organics (C x H y N i O z , abbreviated as CHNO). Specifically, we observed organochlorines including C 2 H 3 ClO 2 , C 3 H 5 ClO 2 , C 4 H 5 ClO 3 , and C 6 H 9 ClO 5 , which were previously measured from environmental chamber reactions of alkanes with chlorine, and C 4 H 7 ClO 3 , C 5 H 9 ClO 2 , C 5 H 9 ClO 3 , C 5 H 9 ClO 4 , C 5 H 7 ClO 3 , C 5 H 11 ClO 3 , C 5 H 8 Cl 2 O 3 , and C 5 H 10 Cl 2 O 2 , which were measured from the reactions of isoprene with chlorine under varying levels of NO x . , As seen in Figures and S8, almost all of the species show similar behavior during phases 2 and 3 of the campaign, where their gas-phase concentrations generally only increase around 7 AM (sunrise), peak around 11 AM to 3 PM, and begin to decline around 6 PM (as solar radiance declines before sunset at 8 PM). The particle phase (FIGAERO) data are shown in the shaded gray areas in Figures and S8.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to molecular chlorine and nitryl chloride, we observed a variety of organic species in the gas and particle phases, including oxygenated organics (compounds with the molecular formula C x H y O z , abbreviated as CHO); chlorinated organics (C x H y Cl i O z , abbreviated as CHClO); and nitrogen-containing organics (C x H y N i O z , abbreviated as CHNO). Specifically, we observed organochlorines including C 2 H 3 ClO 2 , C 3 H 5 ClO 2 , C 4 H 5 ClO 3 , and C 6 H 9 ClO 5 , which were previously measured from environmental chamber reactions of alkanes with chlorine, and C 4 H 7 ClO 3 , C 5 H 9 ClO 2 , C 5 H 9 ClO 3 , C 5 H 9 ClO 4 , C 5 H 7 ClO 3 , C 5 H 11 ClO 3 , C 5 H 8 Cl 2 O 3 , and C 5 H 10 Cl 2 O 2 , which were measured from the reactions of isoprene with chlorine under varying levels of NO x . , As seen in Figures and S8, almost all of the species show similar behavior during phases 2 and 3 of the campaign, where their gas-phase concentrations generally only increase around 7 AM (sunrise), peak around 11 AM to 3 PM, and begin to decline around 6 PM (as solar radiance declines before sunset at 8 PM). The particle phase (FIGAERO) data are shown in the shaded gray areas in Figures and S8.…”
Section: Resultsmentioning
confidence: 87%
“…Reactive chlorine species such as molecular chlorine (Cl 2 ) and nitryl chloride (ClNO 2 ) photolyze in the atmosphere to form chlorine radical (Cl), a potent atmospheric oxidant that impacts air quality by oxidizing VOCs, contributing to the formation of ozone and secondary organic aerosol, and affecting radical budgets. Cl radical oxidizes a wide range of VOCs, often more rapidly than hydroxyl radical (OH), and forms a different set of products than other oxidants. , These include organochlorine species (generally formed when Cl adds to a double bond), which may have substantial health impacts. Furthermore, observations and models show that Cl radicals alter OH and O 3 concentrations. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the importance of chlorine chemistry in coastal areas (Peng et al., 2022; Xue et al., 2015). However, chlorine‐initiated oxidations of unsaturated aliphatic VOCs including isoprene may not lead to OHDCA formation due to the addition of chlorine atom(s) into the main products (Guo et al., 2020; Wang et al., 2022). The ratio of toluene to benzene (T/B) was calculated to examine this effect, as the reaction between benzene and chlorine is very slow (Xue et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorine, when combined with certain metallic components in PM, can lead to the formation of highly reactive chlorine radicals and further enhance oxidative stress in cells. This combined action of metallic components and chlorine can contribute to the development of respiratory inflammation and other health effects in individuals exposed to polluted air 44 .…”
Section: Discussionmentioning
confidence: 99%